Inflammation balance in skeletal muscle damage and repair - Tu, Huiyin; Li, Yu-Long (Frontiers in Immunology, 2023)
Responding to tissue injury, skeletal muscles undergo the tissue destruction and reconstruction accompanied with inflammation. The immune system recognizes the molecules released from or exposed on the damaged tissue. In the local minor tissue damage, tissue-resident macrophages sequester pro-inflammatory debris to prevent initiation of inflammation. In most cases of the skeletal muscle injury, however, a cascade of inflammation will be initiated through activation of local macrophages and mast cells and recruitment of immune cells from blood circulation to the injured site by recongnization of damage-associated molecular patterns (DAMPs) and activated complement system. During the inflammation, macrophages and neutrophils scavenge the tissue debris to release inflammatory cytokines and the latter stimulates myoblast fusion and vascularization to promote injured muscle repair. On the other hand, an abundance of released inflammatory cytokines and chemokines causes the profound hyper-inflammation and mobilization of immune cells to trigger a vicious cycle and lead to the cytokine storm. The cytokine storm results in the elevation of cytolytic and cytotoxic molecules and reactive oxygen species (ROS) in the damaged muscle to aggravates the tissue injury, including the healthy bystander tissue. Severe inflammation in the skeletal muscle can lead to rhabdomyolysis and cause sepsis-like systemic inflammation response syndrome (SIRS) and remote organ damage. Therefore, understanding more details on the involvement of inflammatory factors and immune cells in the skeletal muscle damage and repair can provide the new precise therapeutic strategies, including attenuation of the muscle damage and promotion of the muscle repair.